Redefining the Cost and Complexity of Library Services for Open and Distance Learning - Parnell, Stephen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
Although most universities profess a belief that libraries are a key element in learner support, the full cost and complexity of providing quality library services to support open and distance education tend to be underestimated. It is argued in this article that this underestimation, in part, may reflect a lack of appreciation by faculty and university administrators of the role libraries play in the (distance) learning process. Within libraries and the education sector at large, there is also tends to be a lack of recognition of what portion of the costs of access to libraries and information are borne by other elements within universities, by external organisations, and by individual students. Three fundamental questions addressed are: Why is it necessary to determine the role of libraries in supporting learning? Who meets these costs? How institutionally independent should access to library and information services be? While it is to be expected that the level of costs incurred by different institutions will vary as they meet the library service needs of those who study in different modes, there are pedagogical, ethical, and quality issues that must be considered if the same academic award is to be made.